2011
DOI: 10.1590/s1984-82502011000400024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and toxicity studies of atranorin extracted from Cladina kalbii Ahti in rodents

Abstract: Atranorin (ATR) is the main compound from the lichen Cladina kalbii Ahti, which grows in the arid regions of northeastern Brazil. This study was conducted to evaluate the anti-inflammatory and toxicological properties of ATR. To evaluate anti-inflammatory properties, paw edema was induced by injecting 0.1 mL of carrageenan into the subplantar region of the right hind paw of rats, and leukocyte migration was induced by injection of 500 µL of carrageenan into the peritoneal cavity of mice. In addition, we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Meaning that ATR is more likely to affect the viability of piroplasm parasites rather than host cells. This finding conforms to the report by de Melo et al [8] that ATR lacked toxicity in animal studies. In contrast, Zofou et al [13] showed that ATR had mild cytotoxic action on LLC/MK2 monkey kidney epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Meaning that ATR is more likely to affect the viability of piroplasm parasites rather than host cells. This finding conforms to the report by de Melo et al [8] that ATR lacked toxicity in animal studies. In contrast, Zofou et al [13] showed that ATR had mild cytotoxic action on LLC/MK2 monkey kidney epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas oral administration of HYD and DFMO exhibited a chemotherapeutic effect lower than the 89% and 91% shown by 17-DMAG [28] and nitidine chloride [27], respectively but similar to that shown by trans-chalcone [22]. These results are compatible with those ofde Melo et al [8], who reported the anti-inflammatory activity of ATR, without any significant cytotoxicity in Wistar rats. Although DA is the most effective antibabesial drug used in the veterinary field, it has not been able to remove all parasites from the host animals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results proved the anti-inflammatory properties of atranorin. Moreover, it was stated that the depside is a safe compound, since the experiment conducted in rats showed no symptoms of sub-acute (50 mg/kg/day for 30 days) and acute (5 g/kg) toxicity [8].…”
Section: Anti-inflammatory Activity Of Secondary Metabolitesmentioning
confidence: 99%